FORD FOUNDATION INFLUENCE TOWARDS DEMOCRATIC TRANSITION IN EGYPT DURING ARAB SPRING - Ira Kurnia Maharani (HI 15 UMY 019, 2015)
*19 The Arab Spring started from Tunisia and spread to other countries including Egypt. The uprising was started by some demonstrations toward its government due to poor governance under the dictatorship regime of Mubarak. Furthermore, these uprisings had also brought the idea of democracy to Egypt which famous for its stable authoritarian governmental system. However, the uprisings had attracted global attention and received strong response from various international agents including international NGO, particularly Ford Foundation. NGO as international agents are now recognized as the third key actors in development. Thus, it led Ford Foundation which supported Egyptian to gain their rights to be able to live in peaceful and democratic live where human rights of each people are guaranteed as important actor during that time.